Spatial Assessment of the Recorded Incidents of Mud on the Road in Herefordshire (Global Journal of Science Frontier Research, 2015)
The deposition of mud on the road has serious consequences including contributing to serious and fatal accidents. The objective of this paper was to assess the correlation between reported occurrences of mud on the road in Herefordshire and spatial and temporal factors that may have contributed to the risk of mud ending up on the public highway. Relevant datasets including incidence data (mud on road) from Herefordshire County Council, land use, soil data, erosion risk, slope and data through Digi map online, were combined and spatially analyzed using a GIS (Geographical Information System) software. The results indicated that the highest numbers of mud incidents occurred between October 2013 to April 2014 and 83% of these cases occurred in areas with high erosion risk. The land use data showed that 42% of Herefordshire was arable. Soil data showed that over 74% of the soil texture was silt clay loam which is suitable for arable farming. The data also showed that as rainfall increased mud incidents increased.
Keywords: land use; mud incidents; rainfall; soil texture; slope; erosion